Reframing Transitional Justice: Memory, Interdisciplinarity, and Transformative Ways of Seeing - Ana Forcinito (Latin American Research Review, 2021)
This essay reviews the following works: The El Mozote Massacre: Human Rights and Global Implications. By Leigh Binford. Revised and expanded ed. Tucson: University of Arizona Press, 2016. Pp. 400. $34.95 paperback. ISBN: 9780816532162.   Stories of Civil War in El Salvador: A Battle over Memory. By Erik Ching. Chapel Hill: University of North Carolina Press, 2016. Pp. 362. $34.95 paperback. ISBN: 9781469628660.   The Politics of Transitional Justice in Latin America: Power, Norms, and Capacity Building. By Ezequiel A. González-Ocantos. Cambridge: Cambridge University Press, 2020. $18.00 paperback. ISBN: 9781108799089.   The Feathers of Condor: Transnational State Terrorism, Exiles and Civilian Anticommunism in South America. By Fernando López. Cambridge: Cambridge Scholars Publishing, 2016. Pp. 375. £57.99 hardcover. ISBN: 9781443897099.   Eruptions of Memory: The Critique of Memory in Chile, 1990–2015. By Nelly Richard. Translated by Andrew Ascherl. Pp. xxvi + 189. Cambridge: Polity Press, 2018. Pp. 224. $22.95 paperback. ISBN: 9781509532285.   Exile, Diaspora, and Return: Changing Cultural Landscapes in Argentina, Chile, Paraguay, and Uruguay. By Luis Roniger, Leonardo Senkman, Saúl Sosnowski, and Mario Sznajder. Pp. 304. $82.00 hardcover. Oxford: Oxford University Press, 2018. ISBN: 9780190693961.   Surviving State Terror: Women’s Testimonies of Repression and Resistance in Argentina. By Barbara Sutton. New York: New York University Press, 2018. Pp. v + 325. $35.00 paperback. ISBN: 9781479829927.   Memory, Truth, and Justice in Contemporary Latin America. Edited by Roberta Villalón. Lanham, MD: Rowman and Littlefield, 2017. Pp. vi + 274. $41.00 paperback. ISBN: 9781442267251.